Preoperative tumor marking with indocyanine green (ICG) prior to minimally invasive colorectal cancer: a systematic review of current literature - Konstantinidis, Michael K.; Ioannidis, Argyrios; Vassiliu, Panteleimon; Arkadopoulos, Nikolaos; Papanikolaou, Ioannis S.; Stavridis, Konstantinos; Gallo, Gaetano; Karagiannis, Dimitrios; Chand, Manish; Wexner, Steven D.; Konstantinidis, Konstantinos (Frontiers in Surgery, 2023)
Aim: To describe the currently available evidence regarding the efficacy and safety of preoperative tumor marking using indocyanine green (ICG) prior to laparoscopic or robotic colorectal resections. Methods: A systematic search for relevant studies was conducted using the following databases: Embase (OVID), MEDLINE® (OVID), APA PsycInfo (OVID), Global Health (OVID) This is a provisional file, not the final typeset article and HMIC Health Management Information Consortium (OVID) through June 2022 reported according to PRISMA 2020 guidelines. Primary outcome was the detection rate of the tumor sites preoperatively marked with ICG. Secondary outcomes were timing of ICG injection in days prior to the operation and technique-related complications.Results: Eight single center studies, published between 2008 and 2022, were identified yielding a total of 1061 patients, of whom 696 were preoperatively tattooed with ICG. Injection dosage of diluted ICG ranged from 0.1-1.5ml. Four studies used the saline test injection method prior to ICG injection. When the marking was placed within one week, the visualization rate was 650/668 (97%), whereas when it was longer than one week, the detection rate was 8/56 (14%). No severe complications were reported.Conclusion: Preoperative tumor marking using ICG prior to minimally invasive colorectal resections is safe and effective, allowing intraoperative tumor site location when performed up to a week prior to surgery without disturbing the surgical view in potential mild complications.